Gambaran Sonopattern Dinding Kandung Empedu pada Pasien dengan Cholelithiasis dan Cholecystitis - Kurniawan, Selamet Budi; Hidayat, Wahyu; Nurbaiti, Nurbaiti; Supriyono, Puji; Heru, Nursama (Jurnal Kesehatan, 2023)
Finding cases of cholelithiasis and cholecystitis is not always easy. The sonopattern image from the ultrasound plane (USG) helps doctors diagnose both. Cases characterized by gallbladder abnormalities can be observed through ultrasound examination techniques and the analyze the sonopattern characteristics and thickness of the gallbladder wall. This qualitative research uses secondary data from the National Brain Center Hospital Jakarta. The data from 20 samples were from 10 cholelithiasis patients and ten cholecystitis patients. The results of the sonopattern analysis showed that the group of patients with cholecystitis had an average gallbladder wall thickening. In contrast, the group of patients with cholelithiasis, on average, did not experience thickening of the gallbladder wall.